Abordagens do conceito de “sequência didática” em teses na área de educação matemática - COSTA, Dailson Evangelista (Universidade Federal de Mato Grosso, 2022)
This investigation aims to understand the different approaches of the concept of Didactic Sequence present in doctoral theses, in the area of Mathematics Education, defended in Brazil from 2001 to 2018. This is a bibliographic research of a qualitative nature. We selected 31 doctoral theses available in the portal of theses and dissertations of Capes. Theses were analyzed based on the following criteria: (a) objectives, (b) synthesis of methodology, (c) main results and (d) main references on "Didactic Sequence". The criteria mentioned led us to organize and systematize 5 (five) focuses related to theses regarding the approach of the concept of Didactic Sequence (DS). They are: i) focus of SD in the teaching and learning of basic education students; ii) focus of SD on basic education students and teacher training; iii) focus of SD in teaching and learning of higher education students (Bachelor/Engineering); iv) Focus of SD on Special Education; and v) focus of SD on bibliographic survey. The results indicate twelve characteristics of the approaches on Didactic Sequence, among which we highlight: diversity of theories that give basis to the use of DS; approach to DS as a teaching methodology; lack of theoretical deepening and discussion about the concept of DS; use of DS to improve the teaching and learning process; SD contributes to promote situations that students can act on the activities built and thought by the teacher; SD is used, constructed and developed, in most researches, by the researcher and is not generally constructed by the teacher who will use it in his classroom practices, either teachers in initial training (in degrees) or in continuing education (in service in Basic Education).